KONVERGENSI MEDIA HARIAN METRO RIAU DALAM MENGHADAPI PERSAINGAN INDUSTRI MEDIA - Pelican Landri; Suyanto Suyanto; Yasir Yasir (Jurnal Ilmu Komunikasi, 2018)
Media competition and the development of Information and Communication Technology (ICT), which brings a new trend in the world of the communications industry. Instrument to deal with it is the convergence oriented to the interests of consumers. Media who had converged also affect the amount of economic interests in the application of convergence. Data collection is done by observation and in-depth interviews and review of the literature. Descriptive analysis showed that the strategy Multichannel and Multiplatform) used Metro Riau be one alternative strategy for implementing the convergence and transforming itself towards current development. Uniformity of content among media that are under the Metro Riau and Halloriau.com will benefit through the supply of advertisers, as well as spatialization that enables the distribution of news content in real time can reduce labor costs, administrative and material. The conclusion from this study is that convergence is the convergence contextual done that convergence is tailored to the needs and conditions of the corporate culture and society. It proved convergence can be accomplished without a radical change by uniting print and online newsrooms, media have to do convergence.